2009
DOI: 10.1111/j.1349-7006.2009.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‐ion‐induced bystander killing of human lung cancer cells: Role of gap junctional intercellular communication

Abstract: It is thought that heavy-ion radiation therapy is a promising modality of cancer therapy that can deliver higher biological effects on tumors than conventional X-ray radiation therapy, and may also conserve the function of normal organs because of its excellent dose distribution.(1) Recently, excellent clinical results were reported in the treatment of lung cancer, prostate cancer, cancer of the head and neck, and malignant tumors of bone and soft tissue.(2) Heavy-ion has high linear energy transfer (LET) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…GJB6 has been reported to encode one of connexin proteins, connexin 30 (Cx30). Disruption of gap junction or connexin dysfunction has been indicated to be involved in carcinogenic processes in multiple cancers, including lung carcinogenesis [32][33][34]. Intriguingly, the expression of GJB6 was increased in the stage II of LAC, suggesting that GJB6 serves as an enhancer in the proliferation of tumor cells [35], which may be involved in the LAC pathogenesis by disrupting intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…GJB6 has been reported to encode one of connexin proteins, connexin 30 (Cx30). Disruption of gap junction or connexin dysfunction has been indicated to be involved in carcinogenic processes in multiple cancers, including lung carcinogenesis [32][33][34]. Intriguingly, the expression of GJB6 was increased in the stage II of LAC, suggesting that GJB6 serves as an enhancer in the proliferation of tumor cells [35], which may be involved in the LAC pathogenesis by disrupting intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Funayama et al (2005) reported that the number of non-irradiated CHO-K1 cells in colonies decreased at 60 h after exposure to a high-LET Ar-ion microbeam (11.5 MeV/n, 1260 keV/μm) via the bystander response, using heavy-ion microbeams at the TIARA. The bystander cell killing effect was also reported in A549 (human lung cancer cell line) cells and AG01522D cells after exposure to carbon ions (18.3 MeV/n, 103 keV/μm) or neon ions (13.0 MeV/n, 375 keV/μm) Harada et al, 2009). In these studies, clonogenic survival decreased by about 10%.…”
Section: Discussionmentioning
confidence: 82%
“…An additional excellent feature of the TIARA facility is that the same particles with similar energy in the broadbeams and microbeams can be used to expose biological materials, thereby contributing significantly to the understanding of heavy-ion-induced bystander responses (Shao et al, 2003;Funayama et al, 2005;Kanasugi et al, 2007;Hamada et al, 2008;Iwakawa et al, 2008;Harada et al, 2009;Fournier et al, 2009;Hino et al, 2010;Mutou-Yoshihara et al, 2012;Autsavapromporn et al, 2013 and so on). The significant role of NO in the bystander response was determined in studies using heavy-ion microbeams (Kanasugi et al, 2007;Mutou-Yoshihara et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Studies of bystander effects in cell cultures exposed to low fluences of HZE particles are only emerging, and conflicting data have been reported. In early experiments with a microbeam, stressful effects were shown to be propagated from HZE particle-irradiated cells to contiguous bystander cells (125,127,256). In addition, when HZE particle-irradiated cells were cocultured with bystander cells in a manner in which they shared only the growth medium, stressful responses were also induced in the bystander cells and were similar in nature to those generated in the targeted cells (95,278,(298)(299)(300) (Fig.…”
Section: Space Radiation-induced Nontargeted Effectsmentioning
confidence: 75%
“…The lack of clear knowledge about nontargeted responses (94,127,299) has been singled out by the U.S. National Academies (1) as one of the important factors limiting the prediction of radiation health risks associated with space exploration. This is because during deep space travel, only a small fraction of cells in the human body experiences extremely dense ionizations created along the tracks of the traversing particles in a given day (62).…”
Section: Space Radiation-induced Nontargeted Effectsmentioning
confidence: 99%